The association between disaster exposure and media use on post-traumatic stress disorder following Typhoon Hato in Macao, China - Brian J. Hall; Ying Xin Xiong; Paul S. Y. Yip; Chao Kei Lao; Wei Shi; Elvo K. L. Sou; Kay Chang; Li Wang; Agnes I. F. Lam (European Journal of Psychotraumatology, 2019)
Background: Direct exposure to natural disasters and related losses are associated with post-traumatic stress disorder (PTSD). It is less clear whether indirect media exposure is associated with PTSD. Objective: This study investigated key exposure-related risk factors for PTSD and examined the effect of media exposure on the prevalence of disaster-related PTSD. Method: Typhoon Hato directly hit Macao on 23 August 2017. It was one of the most serious natural disasters ever to strike southern China. One month after the event, 1876 Chinese university students in Macao were recruited into a cross-sectional study (mean age 20.01 years, SD = 2.63; 66.2% female). Self-reported typhoon exposure, media use and exposure to disaster-related content, and PTSD symptoms were collected using an electronic survey. Univariable analyses assessed associations between risk factors and PTSD, which were then included in a series of multivariable logistic regressions. Results: The prevalence of PTSD was 5.1%. Adjusted models demonstrated that being male (vs female) [adjusted odds ratio (aOR) = 1.68, 95% confidence interval (CI) 1.07–2.63], home damage (aOR = 2.86, 95% CI 1.71–4.78), witnessing people injured (aOR = 2.33, 95% CI 1.36–4.00), and almost drowning during the storm (aOR = 8.99, 95% CI 1.92–41.99) were associated with PTSD. After adjusting for direct exposure, indirect exposure to disaster-related social media content, including information related to drowning victims (aOR = 1.29, 95% CI 1.00–1.67) and residents’ emotional reactions (aOR = 1.98, 95% CI 1.44–2.72), was associated with PTSD. Viewing more information about the storm itself (aOR = 0.37, 95% CI 0.28–0.49) and images of heroic acts (aOR = 0.72, 95% CI 0.55–0.94) were significantly associated with lower odds of PTSD. Conclusion: These findings add to the literature demonstrating that some types of media use and certain media content following a natural disaster are associated with PTSD.